Eriophyes species (Acari: Eriophyoidea) inhabiting lime trees (Tilia spp.: Tiliaceae)—supplementary description and morphological variability related to host plants and female forms - Soika, Grażyna; Kozak, Marcin (Zootaxa, 2013)
Three poorly known species of the subfamily Eriophyinae living on Tilia spp. (Tiliaceae) are illustrated and supplementary descriptions are provided. Two of them, Eriophyes exilis (Nalepa 1892) and Eriophyes nervalis (Nalepa 1918), were re-corded both in vein angle galls on leaves of Tilia platyphyllos Scop. and in erinea on leaves of Tilia tomentosa Moench, Tilia americana L. ‘Moltkei’, Tilia americana var. heterophylla (Vent.) Loudon, Tilia cordata Mill., Tilia japonica (Miq.) Simonk., Tilia petiolaris DC. and Tilia zamoyskiana Wróbl. The third species, Eriophyes tiliae Nalepa 1890, was found in nail galls on leaves of T. platyphyllos, T. americana and T. cordata. All of these Eriophyes species showed noticeable morphological differences between protogyne and deutogyne females in terms of the number of dorsal annuli, location of setae d, length of setae e and 3a, distance between tubercles 3a and the length and pattern of the prodorsal shield. Based on a comparative morphological analysis of this original data with that published by A. Nalepa, new synonyms for the following species are proposed: Erophyes exilis (Nalepa) = Eriophyes leiosoma Nalepa syn. nov.; Eriophyes nervalis (Nalepa) = Eriophyes tiliaceus Nalepa syn. nov., Eriophyes tiliae Nalepa = Eriophyes rudis Nalepa syn. nov. = Eriophyes tomentosae Nalepa syn. nov. A key to all studied Eriophyes species living on lime trees is included.